Application of the STAD Learning Model Assisted by the Gamasia Module to Improve Students' Understanding of Concepts - Purnamasari, Mita; Ardianti, Sekar Dwi; Masfuah, Siti (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
The learning models and media have not been fully employed by teachers to optimize students' understanding of concepts. This research aimed to describe the application of the STAD model assisted by the Gamasia module to increase the conceptual understanding of fifth-grade elementary school students at the State Elementary School of Karang in natural science and Indonesian content. This classroom action research was carried out in the fifth grade with research subjects totaling 43 students. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection techniques employed included observation, documentation, and evaluation tests. Data analysis techniques then utilized quantitative and qualitative analyses. Based on data analysis, students' conceptual understanding in cycle I was 78 and increased in cycle II to 87. Then, the results of each indicator revealed that (1) restating a concept with a score of 82 increased to 84, (2) classifying objects according to certain traits with a score of 68 rose to 89, (3) giving examples and non-examples with a score of 79 grew to 85, (4) presenting concepts in various forms of mathematical representation with a score of 75 raised to 87, (5) developing requirements need or enough of a concept with a score of 87 boosted to 92, (6) using, utilizing, and selecting certain procedures with a score of 86 improved to 91, and (7) applying a concept with a score of 71 enlarged to 81. Thus, it can be concluded that the application of the model STAD assisted by the Gamasia module can improve fifth-grade students' understanding of concepts in natural science and Indonesian subjects